THE GRAMMATICALIZATION AND PRAGMATICALIZATION OF INTENSIFYING ADVERBS IN ENGLISH: A CLOSER LOOK AT ‘REALLY’ - Lucile BORDET (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2024)
Intensifiers in English appear to be at the junction of grammar and lexis thanks to an unachieved process of grammaticalization. They are sometimes also subjected to pragmaticalization processes. This paper discusses the case of the intensifying adverb ‘really’. After laying down the theoretical framework used to analyze the various uses of this intensifying adverb, this paper presents the various uses of really through a corpus-based study. The focus is then put on the criteria that make ‘really’ a grammaticalized adverb before investigating to what extent it can be considered as an instance of pragmaticalization.